Iran and Saudi Arabia in the Middle East: leadership and sectarianism (2011-2017) - Behzad Diansaei (Vestnik RUDN. International Relations, 2018)
Relations between Iran and Saudi Arabia have never been at a desirable level. Iran’s 1979 revolution, the fall of Saddam Hussein in Iraq and the Arab Spring in turn increased the disagreement between the two regional powers. This article examines the relationship between Iran and Saudi Arabia in the Middle East between 2011 and 2017. Both countries claim to have leadership over other Islamic Muslim countries in the Middle East, in which Iran as a Shia state and Saudi Arabia as a Sunni-Wahhabi state have multiple ideological and political conflicts that have drawn opposing interests for each other. As a result, new multifactor regional international situation involving Iran and Saudi Arabia arose, to analyze which it would make sense to apply the general scientific analytical methods (logical, typological, inductive-deductive methods, etc.), and a number of specific methods for direct study of international relations, including those based on a systemic approach. The author examines the two powerful Middle Eastern countries with an emphasis on instrumental sectarianism as an important component of the regional order transformation proсess, understanding Iran as one of the superior powers of the region in the context of Islamic discourse and the same role of Saudi Arabia with strong tendency in the framework of Arab discourse. It was concluded that Iran and Saudi Arabia have ambitions for a larger share of the new Middle East and from the viewpoint of religious perspective, are instrumental in expanding their influence in the Middle Eastern countries.